Vilniaus pijorų spaustuvės užsienio autorių leidiniai - Jackevičienė, Irena (Knygotyra, 1999)
Vilnius Pierists Publishing House, founded in 1754, is known as one of the best publishing houses of the 18th century in the Lithuanian Grand Duchy. Approximately 300 books were published in this publishing house until the end of the century. In the 18th century, when great attention was paid to education, there was significant interest in the publishing of popular scientific literature. Since local society was not able to prepare the necessary textbooks for schools in a short period of time, translated textbooks were used. The 18th-century translations list from Vilnius Pierists Publishing House shows that translations of foreign authors’ works formed 22% of the publications from this house. Secular literature made up 65% of all translations published by Vilnius Pierists Publishing House. Works by foreign authors from the 17th and the beginning of the 18th centuries were translated most often. Translations from French comprised the greatest portion of translations at 61%, from Latin 31%, from Italian 6%, and from English 2%. The translations helped overcome the cultural backwardness of the country more effectively than original literature and supplied the market with desirable books.